Infectivity of chimeric human T-cell leukemia virus type I molecular clones assessed by naked DNA inoculation. - Zhao, T M (1996)
Two human T-cell leukemia virus type I (HTLV-I) molecular clones, K30p and K34p were derived from HTLV-I-infected rabbit cell lines. K30p and K34p differ by 18 bp with changes in the long terminal repeats (LTRs) as well as in the gag, pol, and rex but not tax or env gene products. Cells transfected with clone K30p were infectious in vitro and injection of the K30p transfectants or naked K30p DNA into rabbits leads to chronic infection. In contrast, K34p did not mediate infection in vitro or in vivo, although the cell line from which it was derived is fully infectious and K34p transfectants produce intact virus particles. To localize differences involved in the ability of the clones to cause infection, six chimeric HTLV-I clones were constructed by shuffling corresponding fragments containing the substitutions in the LTRs, the gag/pol region and the rex region between K30p and K34p. Cells transfected with any of the six chimeras produced virus, but higher levels of virus were produced by cells transfected with those constructs containing the K30p rex region. Virus production was transient except in cells transfected with K30p or with a chimera consisting of the entire protein coding region of K30p flanked by K34p LTRs; only the transfectants showing persistent virus production mediated in vitro infection. In vivo infection in rabbits following intramuscular DNA injection was mediated by K30p as well as by a chimera of K30p containing the K34p rex gene. Comparisons revealed that virus production was greater and appeared earlier in rabbits injected with K30p. These data suggest that several defects in the K34p clone preclude infectivity and furthermore, provide systems to explore functions of HTLV-I genes.